1963
DOI: 10.1177/004051756303301201
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Degradation of Cotton Cellulose

Abstract: The photochemical degradation of purified cotton cellulose by ultraviolet light has been studied and the following nonvolatile breakdown products identified: cellobiose, 3-P-D~lucosido-D-arabinose, glucose, and arabinosc. Their formation can be explained by fission of bonds around carbon atoms no. 1 of glucose units, while the initiating step is probably cleavage of the glucosidic linkages. Some evidence for the presence of smaller fragments indicates that fission of carbon-to-carbon boiids nlay also occur, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Volatile and nonvolatile acids were also formed. In a study of the water-soluble products from irradiation of cotton cellulose by Gingras et al (10), glucose, arabinose, cellobiose and f3-D-glucosido-D-arabinose were identified. There was some indication of the presence of glycollic acid and erythrose, but these compounds were not consistently present.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile and nonvolatile acids were also formed. In a study of the water-soluble products from irradiation of cotton cellulose by Gingras et al (10), glucose, arabinose, cellobiose and f3-D-glucosido-D-arabinose were identified. There was some indication of the presence of glycollic acid and erythrose, but these compounds were not consistently present.…”
Section: Discussionmentioning
confidence: 99%
“…, Other fabric samples were purified before exposure by a benzene-methanol ( ---2.5 :1, v/v) Soxhlet extraction for 24 hr (about 18 cycles). This was followed, in some cases only, by three alkali scours with aqueous 1 % sodium hydroxide solution in a nitrogen atmosphere, as reported previously [6]. ' Moisture content measurements were made on the cotton samples which had been treated in the various ways described above, using Canadian Government Specification 4-GP-2, Method 3.…”
Section: Methodsmentioning
confidence: 99%
“…Fortier, Pierre, The Cause and Control of Pilling, Textile Forum, University of North Carolina, June (1965). 6. Gintis, D., and Mead, E. J., Textile Res.…”
mentioning
confidence: 99%